Rainbow of Computer Science Dedicated to Hermann Maurer on the Occasion of His 70th Birthday - Calude, Cristian S.; Rozenberg, Grzegorz; Salomaa, Arto.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book is dedicated to Hermann Maurer on the occasion of his 70th birthday. The title word Rainbow reflects the beauty and variety of the achievements of this outstanding scientist, and also the diversity and depth of current research in computer science. The high admiration that Professor Maurer enjoys in the computer science community all over the world was witnessed by the enthusiastic response received to the request to contribute to this book. The contributors are leading researchers, also representing the diversity of computer science. The research areas included in the book range from Automata, Formal Languages and Computability to various aspects of the Practice of Computer Science, as well as from Algorithmics to Learning. The book consists of a brief Preface describing the achievements of Professor Maurer, followed by twenty articles roughly grouped together according to their topics. Most of the articles are written in a style understandable to a wider audience. The book is useful to anyone interested in recent developments in computer science.
Algorithmics -- Improved Approximations for Hard Optimization Problems via Problem Instance Classification -- Covering and Packing with Spheres by Diagonal Distortion in Rn -- Counting Plane Graphs with Exponential Speed-Up -- Formal Languages and Automata -- Ancient Typefaces and Parametric Weighted Finite Automata -- On Language Decompositions and Primality -- Ancient Typefaces and Parametric Weighted Finite Automata -- On Language Decompositions and Primality -- A Unifying Kleene Theorem for Weighted Finite Automata -- Local Squares, Periodicity and Finite Automata -- P and dP Automata: A Survey -- On the General Coloring Problem -- Learning -- Transdisciplinary Collaboration and Lifelong Learning: Fostering and Supporting New Learning Opportunities -- Towards an Open Learning Infrastructure for Open Educational Resources: Abundance as a Platform for Innovation -- Why E-Learning as It Stands Is Not Enough -- The Practice of Informatics -- Domains: Their Simulation, Monitoring and Control$1 (BA Divertimento of Ideas and Suggestions -- Roots and Stimuli to a New Perception of Informatics -- Towards a New Shape Description Paradigm Using the Generative Modeling Language -- Name Resolution by Rewriting in Dynamic Networks of Mobile Entities -- Maintaining the Personal Style and Flair of Handwriting in Presentation Recordings -- TGV-Fusion -- Secure and Privacy-Preserving eGovernment$1 (BBest Practice Austria -- The Quest for Uncertainty.s
Keywords: Computer science; Information theory; Logic design; Artificial intelligence; Computer Science; Theory of Computation; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Computers and Society